ANALISIS BUTIR SOAL LITERASI MEMBACA PADA INSTRUMEN ASESMEN KOMPETENSI MINIMUM SISWA SMK: ANALISIS BUTIR SOAL LITERASI MEMBACA PADA INSTRUMEN ASESMEN KOMPETENSI MINIMUM SISWA SMK PEKANBARU - Selpi Misda; Muhammad Mukhlis (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The reading literacy AKM tested at the State Vocational Schools of Ariculture calss X was previously not tested beforehand, so the eligibility of the items was not yet know so it was necessary to have the validity and reliability of each of these questions, how was the quality of the questions, whether the validity and reliability requirements had been fulfilled or not. Three is 1 instrument analyzed for the minimum competency assessment for reading literacy, which consists of 25 item. The data obtained Wet analyzed using the item validity test rechnique with person correlation and the cronch alpha reliability test was carried out. This study found the results that 1) item that had validity with good eligibility by 48% Wet declared valid and Three were as many as 52% declared invalid. the 2) the feasibility of the items seen from reliability is stated to have a very high level of reliability by obtaining a cronbach alpha value of 0.731.